Natural resources eco facts - Howell, Izzi (Howell, Izzi. Eco facts., 2020)
Uses illustrated facts and statistics to introduces young readers to natural resources and the threat that humans pose to natural resource consumption and contamination. Offers small steps that readers can take to make a difference. Includes color photographs, a glossary, and further resources.